(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Liver plays a vital role in almost all physiological processes and, injury to liver can affect health. There are various endogenous and exogenous agents present in the environment which directly or indirectly affect the function of liver like drugs, alcohols, xenobiotic compounds etc. Liver cells have ability to repair the damage because of its ability to regenerate new cells and it has various system reduces the toxic effects of chemicals. Due to continuous exposure of these agents, leads to cease the ability of cell to repair and produces ROS in the cells which again cause damage to cells. Liver cirrhosis is the final stage in which it cannot be cured but can be treated. But in the early stage of disease treatment can be possible. Various allopathy medicines are available in the market and are most expensive and have various side effects. Developing a drug from medicinal plants or the use of plant’s part is cost-effective and have less or no side effects. So, in the current study, we evaluate and compare the antioxidant, antiinflammatory and hepatoprotective activities of selected Ficus species of Karnataka namely F. parasitica, F. tsiela, F. microcarpa, F. heterophylla, F. dalhousiae, F. drupacea and F. mollis. Bark and leaf samples were used for the present studies extracted with different solvent hexane, ethyl acetate and methanol. Total phenolic content of selected Ficus species were determined which suggested that F. dalhousiae bark methanolic (FdBM) extract contained high amount of total phenolics compared to all other plant samples. The bioactive molecule isolated was naringenin which belongs to flavonoid group and has very good bioactivity. Again naringenin was used for in vivo hepatoprotective studies in paracetamol-induced hepatotoxicity on rats. Naringenin inhibited the activity of serum biomarkers. So, inhibition of these cytokines revealed the protection of hepatic cells from injuries. In silico studies also revealed the protective role of naringenin as the molecular docking studies suggested that naringenin inhibits the expression of MMP-2, H-RAS GTPase, Human Arginase-2, PROMMP- 2TIMP-2 complex and NF-kappaB, which are responsible for the activation of hepatic stellate cells (HSCs) that stimuli the expression of other cytokines and lead to liver damages. Molecular docking also revealed that the binding of naringenin with IL-10 and IL-13 was very weak and have very low XP GScore, it showed that naringenin doesn’t affect the expression of cytokines which helps in repair mechanism of liver during liver disease as compared with positive control silibilin.